Multicultural Islamic Education for Ex-Terrorists: Paradigms, Orientations, and Approaches (Program Studi Pendidikan Agama Islam, 2022)
Terrorism is a problem that has not been fully resolved in Indonesia. This group still exists and continues to conduct cadres in several areas of this country. This study, therefore, aims to reveal the strategy carried out by the Lingkar Perdamaian Foundation (YLP) in Lamongan in providing guidance to former terrorists and breaking the chain of radical ideology in Indonesia. Qualitative data were obtained from interviews and direct observations with former terrorist actors through qualitative methods. This study succeeded in finding that in the process, YLP convincingly applied the values of multicultural Islamic education oriented to changing the ideology and personality of former terrorists. On the other hand, in the process, education for ex-terrorists was conducted based on an extraordinary paradigm, namely divinity (rabbaniyah), humanity (insaniyah), and nationality (wathaniyah). Islamic education was also conducted using a rational, psychosocial, and life skills approach. This research also contributes to building an Islamic education model designed explicitly for ex-terrorists with three orientations at once: ideological change, self-change, and encouraging them to socialize again with the broader community.